PENGARUH REWARD DAN PUNISHMENT TERHADAP KINERJA KARYAWAN PT BUSINESS TRAINING AND EMPOWERING MANAGEMENT SURABAYA - ASMIRIN NOOR (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2015)
Human resources is one of the most important assets and have a direct impact on an organization. To improve the performance of employees is through employee development, namely the holding of reward and punishment. This study aims to determine which of dominant influence on the performance of employees of PT Business Training And Empowering Management Surabaya. Using purposive sampling method, to choose direct all employees as many as 34 people. Data collection methods used were questionnaires, interviews, and documentation. The analytical method used is the method of multiple linear regression analysis From the results of multiple linear regression analysis stated that the variable reward and punishment simultaneously affect the performance of employees of PT Business Training And Empowering Management Surabaya. In partial, reward (X1) and punishment (X2) effect on the performance of employees of PT PT. Business Training And Empowering Management Surabaya.